2016
DOI: 10.1159/000438624
|View full text |Cite
|
Sign up to set email alerts
|

All-Trans Retinoic Acid Attenuates Hypoxia-Induced Injury in NRK52E Cells via Inhibiting NF-κB/VEGF and TGF-β2/VEGF Pathway

Abstract: Background/Aims: Hypoxia has recently been proposed as one of the most important factors in progressive renal injury. Hypoxia-induced vascular endothelial growth factor (VEGF) expression may play a critical role in maintaining peritubular capillary endothelium in renal disease. This study was designed to investigate the effect and underlying mechanism of all-trans retinoic acid (ATRA) on hypoxia-induced injury in NRK52E cells. Methods: For mimicking hypoxia, cells were treated with 100 µM of cobalt chloride (C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 19 publications
(23 reference statements)
0
9
0
Order By: Relevance
“…Retinoids are natural and synthetic derivatives of vitamin A (retinol) [9]. The discovery of all-trans retinoic acid (ATRA) as the carboxylic acid form of vitamin A led to studies that ascribed virtually all of the biological effects of vitamin A to this natural retinoid [12]. Thus, ATRA plays a vital role in normal embryogenesis and in such postnatal processes as skin and epithelial homeostasis, hematopoiesis, and spermatogenesis [34].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Retinoids are natural and synthetic derivatives of vitamin A (retinol) [9]. The discovery of all-trans retinoic acid (ATRA) as the carboxylic acid form of vitamin A led to studies that ascribed virtually all of the biological effects of vitamin A to this natural retinoid [12]. Thus, ATRA plays a vital role in normal embryogenesis and in such postnatal processes as skin and epithelial homeostasis, hematopoiesis, and spermatogenesis [34].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it was found that retinoids could inhibit inflammation, thrombosis, platelet adhesion and aggregation, and stimulate fibrinolysis [11]. Predominantly, all-trans retinoic acid (ATRA) and its stereoisomer 9-cis retinoic acid (9cRA) were found to be very potent metabolites of retinol, exerting pleiotropic effects on many different biological processes [12]. These effects are mediated by binding to retinoic acid receptors (RARs) and retinoid X receptors (RXRs), which are ligand-dependent transcription factors that belong to the nuclear receptor superfamily [13].…”
Section: Introductionmentioning
confidence: 99%
“…On the basis of the known role of ATRA in attenuating hypoxia-induced injury in non-trasformed cells [ 28 ], its possible role in counteracting the effect of low oxygen availability in non-invasive breast cancer cells was investigated. MCF10DCIS cells were then cultured under moderate hypoxia for 96 h in the presence of 1 μM ATRA, revealing an agonist induced decrease of cell growth similar to that observed under normoxia (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Ang and VEGF are two major proangiogenic factors that synergistically promote angiogenesis [27]. The expression level of VEGF is significantly increased in pathological conditions such as hypoxia and injury [28,29]. Studies have Fig.…”
Section: Discussionmentioning
confidence: 99%